PELESTARIAN GREBEG LAWU TAWANGMANGU SEBAGAI UPAYA MELESTARIKAN KEARIFAN LOKAL - Widyaningtyas; Ardian Pamungkas (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2022)
This era's rapid development has had a significant impact on all aspects of life, both socially and economically, as well as culturally. Local wisdom is everything that characterizes a region, whether in the form of food, customs, dances, songs, or regional ceremonies. Tawangmangu is located on the slopes at the foot of Mount Lawu, precisely in Karanganyar regency. Grebeg Lawu, which is an annual event, is held in the context of the anniversary of Karanganyar Regency, which is celebrated with dance performances, ludruk, ketoprak, wayangan, and also kawaritan. The method used is qualitative. Data collection is carried out by observation and in-depth review regarding the preservation of Grebeg Lawu local wisdom in the Tawangmangu area. The Bukit Pengharapan Christian Business and Technology Institute has made a commitment to preserving local wisdom in Tawangmangu. The purpose of holding Grebeg Lawu is to introduce local wisdom in Tawangmangu to the wider community, with all the characteristics that exist in Tawangmangu, so that Tawangmangu has the characteristics separately to display the beauty that is in it.